A teacher-led motor programme to enhance pre-literacy and motor skills in kindergarten children. Issue 3 (4th May 2021) - Alesi, Marianna; Costa, Sebastiano; Bianco, Antonino; Pepi, Annamaria
ABSTRACT: Structured motor tasks may affect cognitive development by creating a cognitively challenging "enriched environment', giving opportunity for social cooperation, increasing the joy to learn through play, improving the sense of mastery and competence. The study investigated the association between motor and cognitive exercises, through a teacher-led programme, to provide kindergarten children with the skills necessary for school literacy. Using a cluster-randomized trial design with an intervention group (N = 110) and a control group (N = 64), we examined the effects of a 3-month teacher-led motor programme enriched by executive function tasks. In the intervention group, significant gains were found from pre-test to post-test in scores on general literacy prerequisites subscales such as behaviour, motor, linguistic comprehension, oral expression, metacognition. Results suggest the need to implement new and enjoyable ways of teaching to enhance children's school readiness through motor activities. Abbreviations : PA=Physical Activity; PMA=Programma Motorio Arricchito (Enriched Motor Programme)